Tracking down the molecular architecture of the synaptonemal complex by expansion microscopy - Fabian U. Zwettler (Nature Portfolio, 2020)
The authors test expansion microscopy protocols for investigation of the molecular organisation of mammalian synaptonemal complexes (SCs) with structured illumination microscopy. They show that the molecular structure is preserved during expansion and ultrastructural details of SCs can be revealed.